Remaja Sehat, Prestasi Hebat! Edukasi Video Kreatif untuk Pencegahan Anemia di MTs Tegalpanjang: Healthy Teens, Outstanding Achievements! Creative Video Education to Prevent Anemia at MTs Tegalpanjang - Fatmawati, Ariani; Imansari, Bhekti; Sanusi, Santy; Astuti, Endang Puji; Fathurahman, Mohammad Najmi; Arsy, Najma Shakiyya Alia; Rahmayanti, Ristina Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Anemia is one of the problems in adolescents in Indonesia, especially female adolescents. One of the causes of female adolescents experiencing anemia is due to menstruation. The purpose of this community service activity is to determine the level of knowledge of female adolescents regarding anemia and hemoglobin (Hb) values. The method in the community service activity is to provide education about anemia and adequate nutrition, pretest-posttest, and blood hemoglobin examination. The media used for education is video and knowledge measurement with a knowledge instrument. This activity was carried out at the Madrasah Tsanawiyah Tegalanjang. The number of female students is 17 students. The results of the activity showed that 88.24% of female adolescents had good knowledge after being given education. The average hemoglobin level of female adolescents is 14.29 g/dl. In conclusion, providing education through video media can increase changes in the level of knowledge for female adolescents at Tegalpanjang Middle School. This activity needs to be continuously coordinated with the Tegalpanjang Health Center as a follow-up to ongoing activities such as routine provision of blood-boosting tablets and the formation of peer groups.